Five Triisopropylsilyl Substituents in Ara‐β‐(1→2)‐Ara Disaccharide Glycosyl Donor Make Unselective Glycosylation Reaction Stereoselective. Issue 46 (12th December 2022) - Abronina, Polina I.; Malysheva, Nelly N.; Stepanova, Elena V.; Shvyrkina, Julia S.; Zinin, Alexander I.; Kononov, Leonid O.
Abstract: Formation of 1, 2‐ trans ‐arabinofuranoside linkage in arabinans from Mycobacterium tuberculosis using differently protected Ara‐β‐(1→2)‐Ara disaccharide glycosyl donors in the absence of a participating group at O‐2 was studied. The influence of the nature of the protective and leaving groups in glycosyl donors on the efficiency and stereoselectivity of the 1, 2‐ trans ‐arabinofuranosylation was investigated. The efficiency of Ara‐β‐(1→2)‐Ara p ‐tolyl thioglycoside containing five triisopropylsilyl groups in 1, 2‐ trans ‐stereoselective synthesis of a protected tetrasaccharide corresponding to a fragment of the M. tuberculosis arabinan was shown for the first time. On the contrary, the use of glycosyl donors based on Ara‐β‐(1→2)‐Ara containing only benzoyl or both silyl and benzoyl groups led to the loss of stereocontrol. Abstract : The efficiency of Ara‐β‐(1→2)‐Ara p ‐tolyl thioglycoside with five triisopropylsilyl groups in stereoselective synthesis of tetrasaccharide corresponding to a fragment of the M. tuberculosis arabinan was shown. On the contrary, the use of glycosyl donors based on Ara‐β‐(1→2)‐Ara disaccharide with only benzoyl or both silyl and benzoyl groups led to the loss of stereocontrol.